The Integration of Sanad in the Contextual Interpretation of the Qur'an: A Maqasid-Based Perspective: (Integrasi Sanad dalam Penafsiran Kontekstual Al-Qur’an: Sebuah Perspektif Berbasis Maqasid) - Akib, Moh. (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
While contextual approaches frequently lack this epistemic anchor, which raises questions about legitimacy, classical Islamic scholarship emphasizes sanad (chain of transmission) as the primary criterion for authenticating Qur'anic interpretations based on Prophetic traditions. By combining sanad-based validation with maqasid al-shari‘ah (higher objectives of Islamic law), this study offers a compromise that results in interpretations that are both legitimate and pertinent. The framework involves two steps: first, isnad-based validation using isnad and matn criticism to verify textual authenticity (riwayah sahihah); second, maqasid-driven interpretation using the values of public welfare, justice, and mercy to bring meaning into line with modern contexts. By ensuring authenticity comes before contextualization, this "double validation" lessens subjective bias while maintaining epistemic authority. The innovation resides in overcoming the riwayah–dirayah divide using a methodical approach that blends purposive interpretation with authenticity protections. In terms of methodology, the study uses a qualitative-descriptive approach that includes textual analysis of both modern tafsir literature influenced by the maqasidi paradigm and classical hadith sources. It uses hermeneutical interpretation to link textual meaning to socio-historical realities, content analysis to identify themes, and isnad–matn criticism to evaluate reliability. The end effect is a methodology that is both responsive to contemporary issues and steadfast in its adherence to Islamic epistemology, maintaining the normative function of sanad while permitting context-sensitive Qur'anic interpretations.